2022
DOI: 10.1186/s40545-022-00429-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pattern and predictors of self-medication for COVID-19 among residents in Umuahia, Abia State, Southeast Nigeria: policy and public health implications

Abstract: Background COVID-19 has led to restrictions on movements and lockdown measures, which have resulted to higher utilization of over-the-counter drugs compared to prescription-only drugs. This study determined the prevalence, pattern and predictors of self-medication for COVID-19 prevention and treatment. Methods A cross-sectional survey was conducted between October and November 2021 among the residents of Umuahia, Abia State. The respondents were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Regarding the population, 30 studies were conducted targeting the general population ( 8 , 11 , 30 , 31 , 34 36 , 38 , 40 , 42 , 44 , 47 , 49 51 , 54 57 , 61 , 63 , 65 , 67 , 68 , 70 , 72 , 75 , 79 , 81 , 83 ), 10 was conducted in students ( 10 , 33 , 39 , 41 , 43 , 53 , 58 , 60 , 71 , 78 ), four in dental visit ( 12 , 29 , 45 , 46 ), three in healthcare workers ( 9 , 80 , 82 ), three in individuals visited medical stores and medical store owners ( 73 , 76 , 77 ), two in older adult ( 28 , 48 ), two in patient ( 27 , 66 ), one in COVID-19 recovered patients ( 52 ), one in mothers with school-age children ( 32 ), one in pregnant and breastfeeding women ( 62 ), one in pregnant and postpartum women ( 64 ), one in adults with a history of taking allopathic medication in the last month ( 37 ), one in five doctors with different specialties (interviews) and adults (survey) ( 59 ), one in people with symptoms related to anxiety and depression ( 69 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the population, 30 studies were conducted targeting the general population ( 8 , 11 , 30 , 31 , 34 36 , 38 , 40 , 42 , 44 , 47 , 49 51 , 54 57 , 61 , 63 , 65 , 67 , 68 , 70 , 72 , 75 , 79 , 81 , 83 ), 10 was conducted in students ( 10 , 33 , 39 , 41 , 43 , 53 , 58 , 60 , 71 , 78 ), four in dental visit ( 12 , 29 , 45 , 46 ), three in healthcare workers ( 9 , 80 , 82 ), three in individuals visited medical stores and medical store owners ( 73 , 76 , 77 ), two in older adult ( 28 , 48 ), two in patient ( 27 , 66 ), one in COVID-19 recovered patients ( 52 ), one in mothers with school-age children ( 32 ), one in pregnant and breastfeeding women ( 62 ), one in pregnant and postpartum women ( 64 ), one in adults with a history of taking allopathic medication in the last month ( 37 ), one in five doctors with different specialties (interviews) and adults (survey) ( 59 ), one in people with symptoms related to anxiety and depression ( 69 …”
Section: Resultsmentioning
confidence: 99%
“…The study showed that women and the 30-40 age group practiced self-medication. 23 This finding is also supported by basic health research conducted by the Ministry of Health of the Republic of Indonesia.…”
Section: Discussionmentioning
confidence: 56%
“…54,55 Nevertheless, limited healthcare infrastructure might push some towards self-medication. 56,57 Self-medication is 58 Another study done in Nigeria also reported a prevalence of 41% for self-medication, which was influenced by factors such as fear of stigmatization, quarantine, and infection. 39 A third study found that during the COVID-19 pandemic, 62.7% of participants in various African countries practiced self-medication.…”
Section: Discussionmentioning
confidence: 99%